So little for the mind - Neatby, Hilda (Clarke, Irwin, 1953)
Including many professional educators, found the indictment not only basically unjust but expressed in harsh and even hysterical terms. Unfortunately most of the written replies which appeared in numerous educational and other periodicals were themselves somewhat hysterical. There was an unfortunate failure on the part of any leading professional educator to give a calm and reasoned reply